Education of Social Work Specialists: Different Models and Possibilities for Lithuania - Buzaitytė-Kašalynienė, Jolita (Acta Paedagogica Vilnensia, 2002)
The aim of this article was to analyse and compare different social work specialist's education models and study programs. There were used comparative analysis and document analysis research methods. The concept “social work specialists” consisted of social workers, social pedagogues and social educators. Lithuanian, German and American social work specialist's education models were discussed and compared. The analysis of different education models was impotent because it showed possibilities for Lithuania. Because different Lithuanian high and higher schools were learning and taking experience from different countries education systems of social work specialists there was a combination of two different education models: at High school and University levels in Lithuania and there were several professional qualifications of social work specialists: social worker, social pedagogue and social educator. Study programs of five universities and two higher professional schools were analysed in comparison with Qualification Requirements for Social Pedagogues. All analysed programs didn't meet some requirements. The analysis of social work education in Lithuanian was important because it allowed further progress and development of study programs and social work profession.
Keywords: Social work specialists; education models; study programs; qualification requirements; professional standards.